Preparing the successful coach - Garrett, Matt (Jones and Bartlett, 2008)
This easy-to-read guide prepares future coaches of all levels and all sports for scenarios and issues they will encounter during their careers. Preparing the Successful Coach provides instructors and students with a springboard to discuss issues that are often overlooked in coaching preparation programs. Students are able to look at scenarios from multiple viewpoints and learn to problem solve effectively